Congenital rubella after previous maternal immunity. Issue 5 (May 1990) - Das, B D; Lakhani, P; Kurtz, J B; Hunter, N; Watson, B E; Cartwright, K A; Caul, E O; Roome, A P
Abstract : Two mothers who had asymptomatic rubella infection in pregnancy gave birth to severely affected infants. In both, the presence of preexisting antibody was well documented, although it could not be established whether it was the result of vaccine or natural infection.